МЕХАНІЗМИ ПЕРЕХОДУ ДО ІННОВАЦІЙНОГО ТИПУ СОЦІАЛЬНО-ЕКОНОМІЧНОГО РОЗВИТКУ РЕГІОНУ - Клевчік, Леонід; Антохов, Андрій (My University, 2022)
Research as elements of the formation of the national innovation system of existing and promising mechanisms for the transition to an innovative scenario for the development of economic and social sectors at the regional level determines the need to analyze the processes of implementation of state innovation policy in a regional projection and study different points of view on, which infrastructural elements of the development of innovation activity in the economic and social sectors of a particular subject can serve as generally accepted mechanisms for the transition to the formation of regional innovation systems. The innovative type of socio-economic development of territories is defined as the formation of long-term multi-level relations between socio-economic entities based on the ideology of innovation culture, which ensures the creation and implementation of innovations in all spheres of life, as well as an increase in intellectual capitalization as a condition for socio-dominant self-development. The goals of the regional innovation system have been developed. The general goal is to increase the competitiveness of the regional economy, the goals of the first level are the formation of regional clusters, the system of strategic planning and programming, the mechanism of public – private partnership, the development of territories, the reform of education, health and housing, the development of small and medium-sized innovative businesses. It is determined that the main documents regulating the issues of innovative development at the regional level are: strategies of regional socio-economic development, laws on innovation, regional target programs for innovation development. This article explains the purpose of the innovative type of society and region, found a new meaning of innovative development of the region. Selected the main effects of innovative development of regions of Ukraine, education and employment. Defined the functional significance of the regional economy in the context of stimulation of innovative development processes. The competitiveness of the regional economy is determined on the basis of a rational combination of economic and civic position with state and social justice.
THE MECHANISMS OF TRANSITION TO THE INNOVATIVE TYPE OF SOCIO-ECONOMIC DEVELOPMENT OF THE REGION
Keywords: самоменеджмент; інформаційний менеджмент; інноваційний розвиток; управління змінами; стратегії бізнесу; макроекономіка; соціально-економічний розвиток